Analysis Of Factors Affecting The Income Of Street Vendors In Kelok Sembilan - Fadila, Nadya; Lukman, Lukman; Resipratiwi, Resipratiwi; Musbatiqsrivani, Musbatiqsrivani (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
This study aims to determine the effect of the variable capital, length of business, and working hours, on the income of street vendors in Kelok Sembilan. This type of research is a quantitative research, namely a study that aims to obtain evidence of a hypothesis. Data collection was carried out by means of interviews and questionnaires as well as direct observation. The samples used were 40 street vendors with Roscoe's theory In analyzing used multiple linear regression analysis techniques. The results of the study show that by testing the regression coefficient partially (t test) with α = 5%, it shows that based on the t test results table above, it can be seen that based on the significance value (Sig.) of the capital variable of 0.061 > probability 0.05, it can be said that there is no the influence between the capital variable and the income variable, the length of business variable is 0.011 <probability 0.05, it can be said that there is an influence between the length of business variable on income. Judging from the working hours variable, the significant value (Sig.) 0.036 > probability 0.05 means that there is an influence between the working hours variable and income. Based on the results of the regression in the table, it shows the influence of the variables Capital (X1), length of business (X2), and working hours (X3), on the income of street vendors (Y) with a calculated F value of 2.86626 with a significance of 0.005 which is smaller than the level the significance used in this study is 0.05 (0.005 <0.05). This shows that the three independent variables simultaneously have a significant effect on the dependent variable. Based on the results of research that has been done, it is suggested: the income of street vendor entrepreneurs can be increased by increasing business capital, increasing the length of business, and increasing working hours.